1984
DOI: 10.1098/rspa.1984.0079
|View full text |Cite
|
Sign up to set email alerts
|

On roll waves down an open inclined channel

Abstract: Flow down an open inclined channel is considered. Dressler ( Communs pure appl. Math. 2, 149-194 (1949),) using the equations of the shallow water theory augmented by the Chezy formula for drag, has shown that the uniform flow becomes unstable when the Froude number F exceeds 4, and in this case he was able to construct a one-parameter family of discontinuous periodic solutions by piecing together continuous sections of wave profile and a series of hydraulic jump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 3 publications
(12 reference statements)
2
51
0
2
Order By: Relevance
“…Two main approaches can be followed to establish the stability criteria of the plane-parallel flow: first, the hydraulic one, which finds long travelling-wave solutions for Froude numbers above 2 by means of the shallow-water equations (e.g. Jeffreys 1925;Dressler 1949;Needham & Merkin 1984;Hwang & Chang 1987;Yu & Kevorkian 1992;Chang, Demekhin & Kalaidin 2000); second, on the basis of the linearized Reynolds equations for a turbulent flow, with critical Froude numbers varying between 1.1 and 1.4 as the Reynolds number is varied over the realistic range of values 2 × 10 3 -10 5 (Demekhin, Kalaǐdin & Shapar' 2005). The effect of bottom topography on the stability of a turbulent flow over uneven surfaces was recently explored by Balmforth & Mandre (2004) following the hydraulic approach, who found that low-amplitude topography destabilizes turbulent roll waves and lowers the critical value of the Froude number required for instability.…”
Section: Introductionmentioning
confidence: 99%
“…Two main approaches can be followed to establish the stability criteria of the plane-parallel flow: first, the hydraulic one, which finds long travelling-wave solutions for Froude numbers above 2 by means of the shallow-water equations (e.g. Jeffreys 1925;Dressler 1949;Needham & Merkin 1984;Hwang & Chang 1987;Yu & Kevorkian 1992;Chang, Demekhin & Kalaidin 2000); second, on the basis of the linearized Reynolds equations for a turbulent flow, with critical Froude numbers varying between 1.1 and 1.4 as the Reynolds number is varied over the realistic range of values 2 × 10 3 -10 5 (Demekhin, Kalaǐdin & Shapar' 2005). The effect of bottom topography on the stability of a turbulent flow over uneven surfaces was recently explored by Balmforth & Mandre (2004) following the hydraulic approach, who found that low-amplitude topography destabilizes turbulent roll waves and lowers the critical value of the Froude number required for instability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Needham & Merkin (1984) examined the role of horizontal friction within the onelayer shallow-water context. Kranenburg (1992) showed that the weakly nonlinear development of a marginally unstable flow could be described by a modified Burgers equation similar to that proposed by Novik (1971).…”
Section: Introductionmentioning
confidence: 99%
“…We conclude by pointing out that the present work, as well as [3], could be extended by the inclusion of a further term in the momentum balance equation (4) that accounts for energy dissipation by shearing normal to the flow, as Needham and Merkin [10] did with Dressler's solution. So unrealistic extreme short wavelengths could be attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…is always larger than 2 for φ > 0 and tends to the critical value of the plane-parallel flow of 2 [10] as φ → 0 (see Fig. 2(a)).…”
Section: Introductionmentioning
confidence: 99%